In vivo 1H MRS of human gallbladder bile in understanding the pathophysiology of primary sclerosing cholangitis (PSC): Immune‐mediated disease versus bile acid‐induced injury. (8th February 2019) - Mohajeri, Sanaz; Bezabeh, Tedros; Ijare, Omkar B.; King, Scott B.; Thomas, Michael Albert; Minuk, Gerald; Lipschitz, Jeremy; Kirkpatrick, Iain; Micflikier, Allan B.; Summers, Randy; Smith, Ian C.P.
Abstract : Primary sclerosing cholangitis (PSC) has been considered to be either an "autoimmune disease" or a "bile acid‐induced injury." In vitro MRS studies on PSC patients have limitations due to the contamination of bile with contrast agent (commonly administered during endoscopic retrograde cholangiopancreatography) and/or the use of patient cohorts with other diseases as controls. The objective of this study was to quantify biliary metabolites using in vivo 1 H MRS and gain insight into the pathogenesis of PSC. Biliary metabolites in 10 PSC patients and 14 healthy controls were quantified in vivo using 1 H MRS on a 3 T MR scanner. The concentrations of total bile acids plus cholesterol, glycine‐conjugated bile acids, taurine‐conjugated bile acids, and choline‐containing phospholipids (chol‐PLs) were compared between the two groups. There were statistically significant decreases in the levels of the above mentioned biliary metabolites in the PSC patients compared with controls. The reduction in bile acid secretion in bile of PSC patients indicates accumulation of bile acids in hepatocytes. Moreover, reduction in the levels of chol‐PLs in bile may increase the toxic effects of bile acids. Our findings suggest that the bile duct injury in PSC patients is most likely due to "bile acid‐induced injury." Abstract : Biliary metabolites – total bile acids (TBAs) plus cholesterol, taurine‐conjugated bile acids (TCBAs), glycine‐conjugated bile acids (GCBAs), and choline‐containing phospholipids (chol‐PLs) – were quantified in primary sclerosing cholangitis (PSC) patients and healthy controls, using in vivo 1 H MRS at 3T. A significant reduction in all the above metabolites was observed in PSC patients compared to controls. The reduction in the levels of bile acids indicates their accumulation in hepatocytes, while the reduction in the chol‐PLs may enhance the toxic effect of accumulated bile acids, supporting the hypothesis that bile duct damage is due to 'bile acid‐induced injury'.